Overexpression of MiR-188-5p Downregulates IL6ST/STAT3/NLRP3 Pathway to Ameliorate Neuron Injury in Oxygen-glucose Deprivation/Reoxygenation - Hu, Yujie; Wang, Ganlan; Yang, Guoshuai (Current Neurovascular Research, 2024)
BackgroundCI/R, characterized by ischemic injury following abrupt reestablishment of blood flow, can cause oxidative stress, mitochondrial dysfunction, and apoptosis. We used oxygen-glucose deprivation/reoxygenation (OGD/R) induced injury in HT22 and primary mouse cortical neurons (MCN) as a model for CI/R.ObjectiveThis study investigates the role of miR-188-5p in hippocampal neuron cell injury associated with Cerebral Ischemia-Reperfusion (CI/R).MethodsHT22 and MCN cells were induced by OGD/R to construct an in vitro model of CI/R. Cell apoptosis and proliferation were assessed using flow cytometry and the Cell Counting Kit-8 (CCK8). ELISA was conducted to measure the levels of IL-1β, IL-6, and TNF-α. Moreover, the interaction between miR-188-5p and IL6ST was investigated using dual luciferase assay, the expression of miR-188-5p, Bax, cleaved-caspase3, IL-6, Bcl-2, IL-1β, TNF-α, IL6ST, NFκB, NLRP3 and STAT3 was evaluated using RT-qPCR or Western blot, and immunofluorescence was used to analyze the co-expression of p-STAT3 and NLRP3 in neuronal cells.ResultsOGD/R reduced proliferation and miR-188-5p levels and increased IL6ST expression, inflammation, and apoptosis in HT22 and MCN cells. Moreover, miR-188-5p was found to bind to IL6ST. Mimics of miR-188-5p reduced apoptosis, lowered the expression of cleaved-caspase3 and Bax proteins, and elevated Bcl-2 protein expression in cells treated with OGD/R. Overexpression of miR-188-5p decreased the levels of NLRP3 and p-STAT3 in the OGD/R group. Furthermore, the overexpression of miR-188-5p reduced IL6ST, p-NFκB/NFκB, p-STAT3/STAT3, and NLRP3 proteins in OGD/R, and these effects could be reversed by IL6ST overexpression.ConclusionMimics of miR-188-5p were found to inhibit inflammation and the STAT3/NLRP3 pathway via IL6ST, thereby ameliorating injury in HT22 and MCN cells treated with OGD/R in the context of CI/R.
Keywords: inflammation